Pengaruh Aktivitas Penerbangan Militer Terhadap Decision Making Personel Air Traffic Controller Pada Unit Approach di Perum LPPNPI Cabang Pekanbaru - Lestari, Witri Ayu; Sugih Arti, Endang; Putra, Gilang Trio (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
This research was conducted at Perum LPPNPI Pekanbaru, Riau Province in January 2020 - February 2020. The method used in this research is quantitative with correctional methods, the data collection technique uses direct questions and observations made by the author. The study population was all ATC personnel at Pekanbaru branch, amounting to 28 people. The data analysis technique used is the normality test and linear regression test. This study concludes that there is a positive relationship between military aviation activity and personnel decision making at ATC. In the regression test the authors get the results of the correlation value / R relationship which is equal to 0.926. From the calculations on SPSS, the coefficient of determination (R Square) is 0.858, which implies that the effect of the independent variable on the dependent variable is 85.8%.